POLA ANTREAN KAPAL PENANGKAPAN IKAN DI PELABUHAN PERIKANAN KARANGSONG, KABUPATEN INDRAMAYU - Rukmana, Raistsa Robbaanii Sunda; Apriliani, Izza Mahdiana; Putra, Pringgo Kusuma Dwi Noor Yadi; Dewanti, Lantun Paradhita (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2024)
A catch unloading is a fishing vessel activity carried out regularly at the port. The high frequency of unloading activities leads to a long queue which requires fishing vessels to wait in significant time for their unloading turn. One of the fishing ports with a significant waiting time is Karangsong Port, where the unloading queue can reach three weeks. To reduce the waiting time, there is a need to identify the utilization level of unloading facilities and queue patterns, as well as calculate unloading time and its influencing factors at Karangsong fishing port. This case study was focused on vessel queuing patterns, utilization of port facilities and the length of unloading time. Data were collected through direct interviews and observations. Based on the calculation results, the utilization rate of the unloading dock is 20.16%, TPI is 36.63% and the port basin reaches 577.86%. The vessels queue in double lines with a single service facility. The average length of unloading time for >30 GT vessels is 2.60 hours while for ≤30 GT vessels is 11.92% faster which is recorded at 2.29 hours. Factors affecting the length of unloading time incorporate the vessel's size, crew size, number of catches, availability of scales, market demand as well as the vessel's position and number of vessels in the queue. Keywords : Queue, fish unloading, port facilities